Tree Species Composition and Distribution in Sungai Lalang Forest Reserve, Selangor, Malaysia - Sasse, Fadal Farag K; hendrarto, Boedi -; Izzati, Munifatul - (Bioma : Berkala Ilmiah Biologi, 2010)
Species richness, species composition, height, diameter class structure and tree species diversity wereexamined in a 1 plot in lowland tropical rain forest in Sungai Lalang forest reserve, Selangor, Malaysia. However,some of trees with diameter of breast height (DBH) of 5 cm and above were measured and recorded to be analyzed.As a result, all species at the study site were compared with some results which were found equaled abundantaccording to Evenness Index that gave a value of 0.922; Margalef’s Index reflected a value of 17.01. Chaetocarpuscastanocarpus (Euphorbiaceae) was the most important species with an IVI (Important Value Index) of 4.643%,while Euphorbiaceae was the dominant family for the study area with IVI of 14.02%. The recommendation are thestudy area should be managed and protected in the right way to ensure the continued existence and conservation ofMalaysia natural resource